1998
DOI: 10.1002/(sici)1097-4660(1998100)73:2<153::aid-jctb939>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability enhancement of anaerobic digestion through membrane gas extraction under organic shock loads

Abstract: : A novel submerged silicone membrane extraction technique for removing the dissolved gases, and was explored as a method for enhancing CO 2 H 2 , the stability of anaerobic digesters under shock loads. The e †ectiveness of this strategy was demonstrated during a Ðve-fold step increase in the feed concentration from 4 kg m~3 to 20 kg m~3 Chemical Oxygen Demand (COD) to two anaerobic chemostats, a control and a membrane reactor, operating under steady state. Data revealed that membrane extraction of enabled neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Krämer and Conrad (1993) detected a biofilm on a silicone membrane after prolonged incubation (days) in a slurry, and suggested that this would cause overestimation of the dissolved hydrogen concentration due to the growth of hydrogen producers on the membrane. Voolapalli and Stuckey (1998) reported a decrease in the transfer of hydrogen from the bulk liquid through a silicone membrane due to growth on the membrane, and suggested that the silicone membrane attracted and supported the slow-growing methanogenic bacteria. On the other hand, Kuroda et al (1991) reported stable continuous use of a fluorinated ethylene-propylene (FEP) membrane-covered electrode for 24 days in an anaerobic digestion process, and Pauss et al (1990b) reported stable long-term operation of a fuel cell with a Teflon membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Krämer and Conrad (1993) detected a biofilm on a silicone membrane after prolonged incubation (days) in a slurry, and suggested that this would cause overestimation of the dissolved hydrogen concentration due to the growth of hydrogen producers on the membrane. Voolapalli and Stuckey (1998) reported a decrease in the transfer of hydrogen from the bulk liquid through a silicone membrane due to growth on the membrane, and suggested that the silicone membrane attracted and supported the slow-growing methanogenic bacteria. On the other hand, Kuroda et al (1991) reported stable continuous use of a fluorinated ethylene-propylene (FEP) membrane-covered electrode for 24 days in an anaerobic digestion process, and Pauss et al (1990b) reported stable long-term operation of a fuel cell with a Teflon membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it appears that a reduction in floc size to very small diameters is not a priori evidence that the symbiotic association is still not functioning. Indirect evidence for this also comes from work by Voolapalli and Stuckey (1998) who used hydrophobic gas membranes to extract hydrogen from methanogenic cultures. These authors found that the hydrophobic surface attracted methanogens, and that floc sizes decreased to less than 5 µm, but the COD removal was better than the control under shock loads.…”
Section: Pressure-driven External Cross-flow Membranementioning
confidence: 99%
“…The yield of hydrogen production may be increased markedly by blowing of nitrogen (99.99%) into the reactor. In a lab scale anaerobic biohydrogen production system, Voolapalli and Stuckey [20] used silicon-ketone membrane extracting soluble gas for separating H 2 and CO 2 , but the disadvantage of this method is reduction of deoxidization due to the forming of biofilm. Nielsen et al [21] used palladium-silver film reactor that are devoid of nitrogen.…”
Section: Technical Improvement Of Hy Evolution Yield and Ratementioning
confidence: 99%